The Relationship Between Islam and Political Influence in Indonesia Hasan Al-Banna's Perspective - Amir Reza Kusuma; Elia Monika (Maklumat: Journal of Da'wah and Islamic Studies, 2024)
Hasan al Banna, is one of the Islamic figures. His ideas and movements together with the Muslim Brotherhood have stimulated the fighting spirit of the Islamic community so as not to be left behind. Back to life inspired by the Qur'an and Sunnah movement. Although this Islamic renewal figure has died, his thoughts are still in the life of the Islamic community. Therefore, in political thought, Hasan al-Banna connects faith with political activity. Of course a Muslim is not perfect Islam unless he becomes a politician, who has a forward-looking view and pays full attention to issues and race. According to him, Islam must lead to attention to the problems of the nation. Islam is a comprehensive system, covering all aspects of life. However, Islam and Indonesian Politics from time to time continue to develop and improve, of course not apart from the development of Religion and politics in Indonesia in general. Keywords: Hasan Al-banna, Islam and Politics, Indonesia.